2020
DOI: 10.1002/syst.201900062
|View full text |Cite
|
Sign up to set email alerts
|

Front Cover: Autonomous Formation and Annealing of Colloidal Crystals Induced by Light‐Powered Oscillations of Active Particles (ChemSystemsChem 1/2020)

Abstract: The Front Cover shows active Ag3PO4 nanoparticles herding bigger inactive SiO2 particles into colloidal crystals that exhibit oscillatory motion. The crystals disperse then rejoin/reorganize, undergoing “autonomous annealing”. More information can be found in the Communication by A. Altemose et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In addition to inducing clustering for oscillating micromotors, toggling light can drive the reversible self-organization of passive particles (video S9, Figure b). Although an earlier study by us has shown that, under continuous illumination, tracer particles were periodically repelled and attracted from a Ag Janus oscillating motors, regular crystals were never observed, unlike the case with oscillating Ag 3 PO 4 microparticles . However, upon intermittent illumination at 5 Hz, negatively charged SiO 2 microspheres rapidly migrated and assembled around clusters of Ag Janus particles that were stuck on the substrate, forming crystalline clusters within seconds.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…In addition to inducing clustering for oscillating micromotors, toggling light can drive the reversible self-organization of passive particles (video S9, Figure b). Although an earlier study by us has shown that, under continuous illumination, tracer particles were periodically repelled and attracted from a Ag Janus oscillating motors, regular crystals were never observed, unlike the case with oscillating Ag 3 PO 4 microparticles . However, upon intermittent illumination at 5 Hz, negatively charged SiO 2 microspheres rapidly migrated and assembled around clusters of Ag Janus particles that were stuck on the substrate, forming crystalline clusters within seconds.…”
Section: Resultsmentioning
confidence: 74%
“…In this article, we show a prototype micromotor that points to this direction. Our strategy stems from recent reports by the Sen lab and us, where silver (Ag)-containing microparticles show spontaneous and regular oscillations in speeds when immersed in H 2 O 2 and KCl, and illuminated with continuous lighting . Moreover, pioneering experiments by Steinbock et al and Petrov et al suggest rich nonlinear effects of chemical oscillators when subject to temporal light modulation. , Inspired by these earlier studies, we here take oscillating Ag Janus micromotors as a model system and examine the changes in their dynamics, both individually and among a population, when light is applied intermittently (i.e., temporal modulation at a switching frequency of 10 –1 to 10 3 Hz).…”
Section: Introductionmentioning
confidence: 99%